2017
DOI: 10.1002/hed.25031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and hematologic markers as predictors of risk of surgical site infection in patients with head and neck cancer undergoing major oncologic surgery

Abstract: Our study shows that patient nutritional and hematological markers are associated with the risk of surgical site infection after major surgery for head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
3
18
1
Order By: Relevance
“…A low incidence of SSI is directly related to an adequate surgical technique and is commonly used as an indicator of quality and safety in hospital care 17 . The incidence of SSI in this study was 6.4%, higher than the incidence reported by the CDC (3.5%) 18 and lower than that reported in other studies 8 , 9 , 19 – 21 , which have described an incidence of up to 85%. Our patients were mostly men (84% men and 16% women) with a mean age of 65.8 years, in line with what has been reported in other neck surgery studies 22 .…”
Section: Discussioncontrasting
confidence: 78%
“…A low incidence of SSI is directly related to an adequate surgical technique and is commonly used as an indicator of quality and safety in hospital care 17 . The incidence of SSI in this study was 6.4%, higher than the incidence reported by the CDC (3.5%) 18 and lower than that reported in other studies 8 , 9 , 19 – 21 , which have described an incidence of up to 85%. Our patients were mostly men (84% men and 16% women) with a mean age of 65.8 years, in line with what has been reported in other neck surgery studies 22 .…”
Section: Discussioncontrasting
confidence: 78%
“…This observation was consistent with that of previous studies. 5 , 15 , 33 , 34 As an adjuvant therapy for oral cancer, radiotherapy eliminates cancerous cells but also damages healthy cells, leading to problems with wound healing. 14 These side-effects from radiation-induced DNA mutations, microvascular damage and soft tissue fibrosis reduce collagen deposition and angiogenesis during wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In a registry study of more than 2000 patients who underwent laryngectomy, the overall wound complication rate was 10.0% and in adjusted analyses hypoalbuminemia (odds ratio, 1.90; 95% confidence interval, 1.32–2.74) was independently associated with postoperative wound complications; other risk factors were an operative time of more than 10 h, prior exposure to radiation therapy, presence of diabetes, preoperative anemia, and thrombocytosis [ 162 ]. In a study of cancer patients undergoing head and neck surgery, there was a surgical site infection rate of 104/399 (28%); patients with preoperative hypoalbuminemia (<3.3 g/dL) had a 3-fold higher risk of surgical site infection [ 163 ]. In oral cancer surgery, it has also been reported that early postoperative hypoalbuminemia (<2.5 g/dL) is an independent risk factor for the development of surgical site infections.…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%